Anti‐Tumor Activity of Doxorubicin‐loaded Boehmite Nanocontainers. Issue 24 (12th December 2019) - Seidl, Carmen; Simonato, Sara; Zittel, Eva; Schepers, Ute; Feldmann, Claus
Abstract : Doxorubicin‐filled boehmite nanocontainers, DOX@ γ ‐AlO(OH), with a mean diameter of 40 nm and a wall thickness of 10 nm are prepared via a microemulsion strategy and studied as drug carriers for cancer treatment. Nanocontainer structure and drug load are examined in detail based on different analytical tools. The DOX load is optimized on highest load at lowest side effects according to blood counts. Cell uptake, DOX‐based fluorescence detection and systemic toxicity are evaluated based on in vitro and in vivo models. Toxicity and activity of the DOX@AlO(OH) nanocontainers are compared with non‐filled AlO(OH) hollow spheres and free DOX as references and show promising results. An orthotopic breast cancer BALB/c mouse model validates the activity of DOX@AlO(OH) in vivo at lower side effects than for free DOX. Abstract :